THE IMPACT OF URBAN POPULATION CHANGE ON FORESTS, IN-FOREST RECREATION AREAS AND URBAN FORESTS IN TURKEY - Köse, Murat (CORVINUS UNIV BUDAPEST, 2022)
This study aimed to investigate the effects of rapid population growth and urbanization on forests, in-forest recreation areas and urban forests in Turkey. Therefore, through the consideration of the urban population changes in Turkey between 1973-2019, "Forestry Statistics" related to the changes in the forest existence, in-forest recreational areas and urban forests were evaluated. Within the scope of "Forestry Statistics", both forestry data and population data were considered separate variables, and 36 variables were created in this context. According to this, while the total forest area in Turkey was 20,199,296 ha in 1973, it increased by 2,541,001 ha (12.6%) and reached 22,740,297 ha by 2019. According to the up-to-date data, there have been increases in growing stock and annual current increment, as well as forest areas in Turkey. It is a fact that there is a transformation in favor of forests in rural areas of the country. However, it is not possible to talk about a similar situation in urban areas. Although there is a positive correlation between the urban population and forest presence across the country, it is not at the same rate. The urban population increases several times faster than the extent of forest areas and growing stock.
Keywords: urbanization; rural changes; forestry statistics; growing stock; annual current increment; Turkey